Healthcare Supply Chain Framework for Optimization Process: Literature Review and Some Issues - Jeanne Switasarry Alexandrea, Parama Kartika Dewa (International Journal of Advanced Science and Technology, 2020)
At present, conditions throughout the world require good health services, coronavirus attacks make this relevant for further research. Good health services need support from good supply chain management. Performance in the supply chain can be operated well if a framework for the supply chain structure is available. The heathcare supply chain management system will be different when the context and environment are different from normal conditions. In the case of the Covid-19 pandemic the community needs a fast response from hospital services. The speed of the number of patients increases exponentially. This will affect the performance of the manufacturing supply chain where human resources will be reduced exponentially. The limited number of hospitals that are referred to patient care is limited, increasing the complexity of the problems faced by the healthcare supply chain. The challenge that must be resolved is how the available resources are optimized to achieve their main objectives. For the stages of answering this challenge, an appropriate framework is needed. Based on the literature review and interviews with parties involved in the healthcare supply chain, a framework was developed to manage the healthcare supply chain. The main components of the proposed framework include: the objective function, performance indicators, constraints, risk, and players.